2021
DOI: 10.3390/ijerph182412895
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Particulate Matter on All-Cause Mortality in Urban, Rural, and Suburban Areas, Italy

Abstract: Background: Short-term exposure to particulate matter (PM) has been related to mortality worldwide. Most evidence comes from studies conducted in major cities, while little is known on the effects of low concentrations of PM and in less urbanized areas. We aim to investigate the relationship between PM and all-cause mortality at national level in Italy. Methods: Daily numbers of all-cause mortality were collected for all 8092 municipalities of Italy, from 2006 to 2015. A satellite-based spatiotemporal model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…PM 10 has acute effects such as coughing, shortness of breath, chest pain, eye irritation (19−20). Particulate dust has also been shown to be associated with the rapid worsening of chronic obstructive pulmonary disease (COPD) and exerts a harmful effect such as mortality even at very low concentrations (17,21). Hospital visits due to arrhythmia, cerebrovascular disease, high blood pressure, and ischemic heart disease can also be affected by exposure to an increase in 10 μg/m 3 PM 10 concentration.…”
Section: Health Risk Of Pm 10mentioning
confidence: 99%
“…PM 10 has acute effects such as coughing, shortness of breath, chest pain, eye irritation (19−20). Particulate dust has also been shown to be associated with the rapid worsening of chronic obstructive pulmonary disease (COPD) and exerts a harmful effect such as mortality even at very low concentrations (17,21). Hospital visits due to arrhythmia, cerebrovascular disease, high blood pressure, and ischemic heart disease can also be affected by exposure to an increase in 10 μg/m 3 PM 10 concentration.…”
Section: Health Risk Of Pm 10mentioning
confidence: 99%
“…It has been shown that the smaller the particulate matter, the more hazardous it is [ 1 ]. The medical literature reveals lung cancer [ 18 , 19 ], chronic obstructive pulmonary disease [ 20 , 21 ], and other conditions [ 1 , 22 , 23 ] to be caused by carcinogenic compounds, heavy metals, benzo(α)pyrene, and black carbon stemming from the combustion of, i.e., coal in stoves.…”
Section: Introductionmentioning
confidence: 99%
“…Highly spatially-resolved PM 2.5 predictions for exposure assessment along with individual-level health records, allows exploration of effect modification by the inclusion of individual (or area-level shared) characteristics which are difficult to consider when using aggregated data, like in traditional city-wide time-series studies (Wei et al, 2019; Yitshak-Sade et al, 2019). Age, sex, socio-economic status (SES), and race, are among the factors that seem to modify vulnerability to PM 2.5 exposure in high-income countries (Franklin et al, 2006; Heo et al, 2022; Renzi et al, 2021; Wang et al, 2020). Such characteristics are of interest for identification of vulnerable populations, science-based policy and targeted public-health interventions (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%